MICROBIAL BURDEN OF SOME HERBAL ANTIMALARIALS MARKETED AT ELELE, RIVERS STATE - Tatfeng, Y. M.; Olama, E. H.; Ojo, T. O. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Herbal antimalarials still remain an alternative to our traditional communities who can not afford orthodox antimalarials. This study was aimed at investigating the microbial quality of six herbal antimalarials using standard microbiological methods. Of the six preparations analyzed, “schnapps”, palm wine and water were the media of preparation; the water base preparations recorded higher microbial load. The mean microbial load was 159.5x105 cfu/ml and 217.4x102cfu/ml in water and alcohol base preparations respectively. The microbial profile of the preparations showed that the schnapps base preparations were predominantly contaminated with Bacillus sp (Aerobic spore bearers) and Mucor spp. The palm wine preparation harboured Bacillus sp, yeasts and Mucor spp while the water base preparations had several isolates such as Staphylococcus epidermidis, Pseudomonas aeruginosa, Escherichia coli 0157H7, Proteus mirabilis, Enterococcus feacalis, Serratia marcensces, Staph. aureus, Bacillus spp and Mucor spp. Conclusively, this study underlines the public health importance of these preparations given the high burden of such human pathogen as Ecoli O157H7, Ps aeruginosa, Stahp aureus, etc. in the preparations.